054 Dementia mortality in wales: a population-based e-cohort. Issue 12 (14th November 2019) - Wilkinson, Tim; Schnier, Christian; Akbari, Ashley; Orton, Chris; Lyons, Ronan; Sudlow, Cathie
Abstract : Background: The Secure Anonymised Information Linkage Dementia e-Cohort (SAIL-DeC) is composed of anonymised, linked, routinely-collected healthcare datasets for the population of Wales. We used this population-based e-cohort to investigate dementia mortality. Methods: SAIL-DeC uses a validated algorithm to identify all-cause dementia cases from coded primary care, hospital admissions and mortality datasets. We ascertained death dates and causes from mortality data. For dementia cases, we calculated median survival (stratified by 10-year age categories), identified the underlying causes of death and compared 10-year survival rates to people without dementia. Results: From 1.2 million participants, 129, 650 developed dementia. Of these, 102, 388 died during follow-up. Median age at dementia diagnosis was 82 years. Median survival after diagnosis was 12.3 years for ages 50–60, 6.8 years for ages 60–70, 4.2 years for ages 70–80 and 2.4 years for ages 80–90. Ten-year survival rates for dementia cases were lower than those without dementia. The most common recorded underlying causes of death were Dementia/Alzheimer's disease (34%), stroke (13%), ischaemic heart disease (IHD) (9%), influenza/pneumonia (6%) and chronic respiratory diseases (3%). Conclusion: Mortality in dementia cases is higher than non-cases across all ages. The leading causes of death amongst people with dementia are stroke, IHD and respiratory diseases.